Is Cardiac Repolarization Time Different Between Epilepsy Patients On Antiepileptic Drugs and Healthy Subjects? - Kezban ASLAN; Turgay DEMİR; Buğra KARAASLAN; Hacer BOZDEMİR (Archives of Epilepsy, 2018)

(untitled)
Objectives:Sudden unexpected death in epilepsy (SUDEP) is attributed to peri-ictal cardiopulmonary abnormalities. In the present study, epilepsy patients on monotherapy (carbamazepine [CBZ], oxcarbazepine [OXZ], valproic acid [VPA]) were compared with a healthy control group to investigate the effects of epilepsy and various antiepileptic drugs on QTmax, QTmin, and QTd.Methods:Seventy eight (51.3% females) epilepsy patients with a mean age of 32.7±11.4 (range, 17–63) years and 71 (56.3% female) healthy subjects with a mean age of 36.3±13.6 (range, 18–64) years participated in the study. The shorter and longer QT were measured by electrocardiography (ECG) and then differences between them (QTd) were calculated. SPSS for Windows 21.0 package software was used to compare the findings between groups.Results:QTmin (p<0.000), QTmax (p<0.000), and QTd (p=0.069) were longer in the epilepsy group than in the control group. On the other hand, we found that 20 epilepsy patients, and none of the control subjects, had a long QT.Conclusion:In this study, we found that cardiac repolarization parameters were different between epileptic and healthy subjects. These results showed the importance of ECG controls at follow-up of epilepsy patients.